Genevieve's war - Giff, Patricia Reilly; Stadtlander, Becca (New York : Holiday House, 2017)
"In August 1939 Genevieve makes an impulsive decision not to get on train to take her to a boat back to New York and must spend the duration of World War II with her grandmother in a small village in Alsace, France, where she becomes involved with the French resistance"--Provided by publisher.
School Library Journal, April 2017
Booklist starred, March 2017
Kirkus Review, March 2017
Publishers Weekly Annex, February 2017
School Library Journal
Booklist starred
Keywords: World War, 1939-1945 -- Underground movements -- France -- Juvenile fiction; Grandparent and child -- Juvenile fiction; Self-reliance -- Juvenile fiction; World War, 1939-1945 -- Underground movements -- France -- Fiction; Grandparent and child -- Fiction; Self-reliance -- Fiction; World War, 1939-1945 -- Underground movements -- France -- Fiction; Grandparent-grandchild relationship -- Fiction; Self-reliance -- Fiction; France -- History -- German occupation, 1940-1945 -- Juvenile fiction; France -- History -- German occupation, 1940-1945 -- Fiction; France -- History -- 1940-1945, German occupation -- Fiction; Historical fiction